Sexuality in the Swedish Police : From Gay Jokes to Pride Parades. - Rennstam, Jens. (Taylor & Francis Group, 2023)
Sexuality in the Swedish Police is based on the experiences of lesbian, gay and bisexual police officers and the author's observations of police work. The book analyses how processes of exclusion and inclusion of LGB sexuality coexist in the Swedish police.